Herakles- und Theseus-Darstellungen auf Campana-Reliefs Untersuchungen zur Adaption und Tradierung zweier griechischer Helden in römischer Zeit - Möller-Titel, Nathalie (Hamburg University Press, 2019)
The subject of this study are depictions of Heracles and Theseus on Roman terracotta reliefs, also called Campana reliefs. It is based on 16 different motifs, which were established during the middle of the 1st century B.C. The aim of the study is to show how these motifs were received and what meaning lies behind these reliefs regarding the historical background of the late Republic and early imperial period.